2016
DOI: 10.1212/wnl.0000000000002860
|View full text |Cite
|
Sign up to set email alerts
|

Early CT changes in patients admitted for thrombectomy

Abstract: In patients considered for thrombectomy, there may be insufficient agreement between clinicians for ASPECTS to be reliably used as a criterion for treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 23 publications
3
84
0
3
Order By: Relevance
“…However, in our study, we used the Rx‐ASPECTS scored during the acute stroke evaluation reflecting true clinical practice which we consider a strength as compared with retrospective expert reading. The observed low correlation reflects ASPECTS intrinsic limitations previously reported . Finally, we measured FIV on a control CT scan performed 24 hours after onset instead of on a follow‐up magnetic resonance fluid‐attenuated inversion recovery (FLAIR) imaging, which is considered the gold‐standard for FIV measurements.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, in our study, we used the Rx‐ASPECTS scored during the acute stroke evaluation reflecting true clinical practice which we consider a strength as compared with retrospective expert reading. The observed low correlation reflects ASPECTS intrinsic limitations previously reported . Finally, we measured FIV on a control CT scan performed 24 hours after onset instead of on a follow‐up magnetic resonance fluid‐attenuated inversion recovery (FLAIR) imaging, which is considered the gold‐standard for FIV measurements.…”
Section: Discussionmentioning
confidence: 88%
“…In the hyperacute setting, CT images obtained within the first hours of an acute ischemic stroke might present only subtle signs of cerebral ischemia. Therefore, ASPECTS evaluation requires experienced training and even between experts, ASPECTS presents a poor interrater reliability …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, all imaging was reviewed at each site by local investigators without central adjudication. The historically reported inter‐rater reliability of individual patient ASPECTS scores in acute stroke has been poor, but it may improve when the ASPECTS is categorized into two or more groups . For this reason, we grouped patients according to the presence of any early infarct signs (ASPECTS <10) and those with unfavorable ASPECTS scores (ASPECTS <6), which should improve the inter‐rater reliability in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have shown that CT ASPECTS and CT perfusion findings were not independent predictors when reperfusion status was included [11, 38]. CT ASPECTS has limited inter- and intrarater reliability [39] and is less predictive than diffusion-weighted imaging (DWI)-ASPECTS or CT perfusion [40-42]. However, recent studies using MRI DWI-ASPECTS also highlighted the importance of reperfusion status for the prediction of outcome [33, 43].…”
Section: Discussionmentioning
confidence: 99%